Design and fabrication of adjustable wide multifunctional trolley / Muhammad Saiful Aiman Mohd Zin - Mohd Zin, Muhammad Saiful Aiman (2023)
This report is about trolley that have always been widely used in industry. Trolley is the device used for carrying load or to transport the material from one point to another. However, the common trolley that is in the market is not really user friendly because it can harm your back bones that will lead to back pain. To overcome this problem, a new trolley was designed which could be used for multi-purpose function and can also prevent from getting a back pain while lifting and loading goods. This project will come out with a new trolley design that will help users to ease work and without worrying from getting back pain. The selection of suitable materials in the fabricating of this trolley is a loaded material which has minimum weight, long life-span and can detain heavy load. This project is about to design and fabricate a new product of a trolley that has multi-functions. The objectives for this project are to design the adjustable wide multifunctional trolley and to analysis and fabricate the extendable wide multifunctional trolley. This project is made for all ages, such as woman, senior citizen and children able to handle this machine easily.